Medial Meniscus Posterior Root Tear Repair Using a 2-Simple-Suture Pullout Technique - Samy, Tarek Mohamed (Arthrosc Tech, 2017)
Medial meniscus posterior root tear is one of the underestimated knee injuries in terms of incidence. Despite its grave sequelae, using simple but effective technique can maintain the native knee joint longevity. In the current note, a 2-simple-suture pullout technique was used to effectively reduce the meniscus posterior root to its anatomic position. The success of the technique depended on proper tool selection as well as tibial tunnel direction that allowed easier root suturing and better suture tensioning, without inducing any iatrogenic articular cartilage injury or meniscal tissue loss. Using anterior knee arthroscopy portals, anterolateral as a viewing portal and anteromedial as a working portal, a 7-mm tibial tunnel starting at Gerdy tubercle and ending at the medial meniscus posterior root bed was created. The 2 simple sutures were retrieved through the tunnel and tensioned and secured over a 12-mm-diameter washer at the tibial tunnel outer orifice. Anatomic reduction of the medial meniscus posterior root tear was confirmed arthroscopically intraoperatively and radiologically by postoperative magnetic resonance imaging.